On site electrochemical production of sodium hypochlorite disinfectant for a power plant utilizing seawater - Saleem, Muhammad; Chakrabarti, Mohammed Harun; Hasan, Diya'uddeen Basheer; Islam, Md. Sakinul; Yusoff, Rozita; Hajimolana, Sayed Ahmad; Hussain, Mohd Azlan; Khan, G.M.A.; Ali, Brahim Si (Electrochemical Science Group, 2012)
This investigation deals with the application of electrochemical technology for the onsite generation of sodium hypochlorite (NaOCl) from seawater for utilization in the power industry. The interaction at different levels of several variables namely, the electrode type and their surface area ratio, current density, and inter-electrode spacing were monitored. A laboratory scale reactor having two electrodes was fabricated and implemented to achieve the objective. The highest production of NaOCl was obtained using a titanium electrode coated with a dimensionally stable anode (DSA) that gave high-current efficiency and superior durability. Maximum production was achieved using titanium under conditions of 72.4 mA/cm 2 current density, 7 cm inter-electrode spacing and a value of 1 for the anode to cathode surface area ratio. Although at higher surface area ratios, more NaOCl production was observed, the increase in its production was marginal for ratios above unity in comparison to ratios below unity. Hence, a ratio of unity was chosen as a practical value which also reduced the costs of the process. This was found to be similar to, if not better than, results reported in the literature. Optimization studies using design of experiments are recommended in the future.